Mentoring in tutorship: prospects and problems of development in preschool education in the Russian Federation - A. M. Garifullina (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Mentoring in preschool education is a new concept in the context of managing a preschool educational organization. In general, mentoring is an understudied concept for the educational system, so we would like to reveal its aspects and the main types of tools that will allow managers to delegate responsibilities and build trust with teachers. The article reviews domestic and foreign research in the field of scientific foundations of mentoring in tutorship. The aim is to study the components of the developed model “ROST”, to consider the possibility of its application in a preschool educational organization.Materials and methods. The method of communicative core, critical thinking, expert opinion and interviews allowed the authors to study the regions of the Volga region (Chuvash, Mari regions) and the region of the Urals, as well as Udmurtia, Nizhny Novgorod, Kirov, Ulyanovsk, Samara and Penza regions.Results and discussion. After the experiment, all the interviewed managers admitted that prior they treated mentoring and tutorship equally, therefore, when recalling their development as a manager, they recalled a lot about more experienced colleagues who helped them in their professional development and did it in the manner of a “tutor” rather than a “mentor”. The result was that managers recognized the difference between mentoring and tutorship.Conclusion. Mentoring in education is designed to help both novice and experienced educators reveal “hidden” capabilities.